Modeling of fatigue damage accumulation in structural steels under low-cycle block loading - Volkov Ivan Аndreevich; Korotkikh, Yuriy Georgievich; Panov, Vladimir Aleksandrovich; Shishulin, Denis Nikolaevich (Computational Continuum Mechanics, 2014)
The process of low-cycle fatigue of structural steels under arbitrary thermal loading is modeled within the framework of mechanics of defective materials. The development of the model of damaged medium involves three steps: - thermo-plastic equations are derived using the concept of surface creep and its transformation under thermal mechanical loading. This variant of thermo-plastic equations describes the main effects of complex plastic deformation of metals and their alloys; - kinetic equations of fatigue damage accumulation are derived by studying the physical stages of development of micro-defects. The equations are based on energy principles and take into account the influence of deformation path conditions, the type of stress state, and the level of damage accumulation on the rate of accumulation of fatigue damages; - condition for critical damage value is taken as a criterion for macroscopic crack formation. The results of a comparative study of the proposed model and the J.L. Chaboche model underlying the modern finite-element analysis code ANSYS are presented. It is shown that the thermo-plastic equations coincide with each other up to constants, and for regular loading cycles the equations of damage accumulation curve and the failure criterion are identical. The experimental study of fatigue damage accumulation in the laboratory samples made of 08Х18Н10Т austenitic steel subjected to double-block low-cycle loading was carried out. Comparison of the experimental and calculated data shows that the model of damaged media developed by the authors can adequately represent the process of fatigue damage accumulation under block low-cycle loading. The possibility to use the Palmgren-Miner linear damage summation in the case of block loading modes is studied. It has been found that such an approach to calculations of the fatigue life under irregular loading can provide both the conservative and non-conservative assessment of the fatigue life.